A Study on Nomophobia among Students of a Medical College in Malaysia - Mohd Hairulnisam Samsudin; Nur Aisya Abdul Aziz; Nur Fathinah Leman; Muhammad Mu’az Shaharani; Pradeep Palanisamy; Vignesh Ramachandran (Asian Journal of Medicine & Health Sciences, 2021)
Background: The word ‘Nomophobia’ coined from ‘no mobile’ phobia refers to the fear of not being with the phone. Nomophobic person tend to experience a few symptoms of mobile phone withdrawals. This study was designed to evaluate the occurrence of nomophobia, to determine its possible association with sociodemographic determinants and to assess the health-related consequences. Methods: This cross-sectional study was conducted among medical students of UniKL Royal College of Medicine Perak and data were collected from a total of 259 medical students using the standard and validated ‘Nomophobia Questionnaire’ (NMP-Q) to assess nomophobia. Results: The prevalence of nomophobia was 51.0%, which was slightly higher among males (52.2%) compared to females (47.8%). There were significant association between nomophobia and uses of social media apps such as Twitter, Instagram, and WhatsApp. Headache was the main health consequence of nomophobia (62.5%). Money spent on mobile phone was significantly associated with nomophobia. Conclusion: Higher prevalence of nomophobia among the medical students thereby indicating their excessive mobile phone dependence is an issue of concern and could possibly impact their mental and physical health of students. Strategies are to be devised on a priority basis for minimizing nomophobia among the students.